A Surface-Specific Isotope Effect in Mixtures of Light and Heavy Water - Liu, J; Andino, R; Miller, C; Chen, X; Wilkins, D; Ceriotti, M; Manolopoulos, D (2013)
Isotope fractionation between different phases is a subtle but very important phenomenon that is related to the quantum nature of light nuclei, and that has important consequences for geochemistry, hydrology, and biology. Here we present a joint experimental/theoretical investigation of the differential segregation of hydrogen and deuterium at the liquid/vapor interface of mixtures of light and heavy water. We use both vibrational sum-frequency spectroscopy and path integral molecular dynamics simulations to quantitatively assess this phenomenon. The experimental and theoretical results indicate that the last layer of water molecules at the liquid/vapor interface is enriched in hydrogen. We discuss in detail the extent, the physical origin, and the implications of this surface-specific isotope effect. © 2013 American Chemical Society.